Words from the Languages of Places Visited in Travelogues: Indicators of Local Culture - Kerima Filan (Türkiyat Mecmuası)
British travelers who traveled through Bosnia and Herzegovina in the past centuries periodically used words and expressions in their travel writing that belong to the language of the places visited. This paper analyzes these linguistic elements in order to consider which entities of the Bosnian-Herzegovinian reality were marked by foreign travelers’ use of native words. The analysis is based on the theory that, to a travel writer as a speaking subject, an adequacy exists between the entity of reality and the linguistic sign used to signify it. This feature is associated with the nature of the linguistic sign; more specifically, it is associated with the relationship between language and reality. The results of the analysis are evaluated within the framework of the theoretical approach that the subjects written in a travelogue as a cultural text were developed on the basis of observations and that the observations emerged from the comparison of the foreign world and the world to which the travel writer belongs. What travel writers have noted down as different in the places visited is shown to be signaled by the elements of the local language, and these linguistic forms themselves are also shown to establish a strong position in the cognitive construction of the foreign place.